Calcium Phosphate‐Coated and Strontium‐Incorporated Mesoporous Silica Nanoparticles Can Effectively Induce Osteogenic Stem Cell Differentiation. Issue 4 (25th November 2021) - Sutthavas, Pichaporn; Tahmasebi Birgani, Zeinab; Habibovic, Pamela; van Rijt, Sabine
Abstract: Ceramic (nano)materials are promising materials for bone regeneration applications. The addition of bioinorganics such as strontium (Sr) and zinc (Zn) is a popular approach to further improve their biological performance. However, control over ion delivery is important to prevent off‐target effects. Mesoporous silica nanoparticles (MSNs) are popular nanomaterials that can be designed to incorporate and controllably deliver multiple ions to steer specific regenerative processes. In this work, MSNs loaded with Sr (MSNSr ) and surface coated with a pH‐sensitive calcium phosphate (MSNSr ‐CaP) or calcium phosphate zinc layer (MSNSr ‐CaZnP) are developed. The ability of the MSNs to promote osteogenesis in human mesenchymal stromal cells (hMSCs) under basic cell culture conditions is explored and compared to ion administration directly to the cell culture media. Here, it is shown that MSN‐CaPs can effectively induce alkaline phosphatase (ALP) levels and osteogenic gene expression in the absence of other osteogenic stimulants, where an improved effect is observed for MSNs surface coated with multiple ions. Moreover, comparatively lower ion doses are needed when using MSNs as delivery vehicles compared to direct ion administration in the medium. In summary, the MSNs developed here represent promising vehicles to deliver (multiple) bioinorganics and promote hMSC osteogenesis in basic conditions. Abstract : Mesoporous silica nanoparticles (MSNs) loaded with strontium ions (MSNSr ) and surface coated with a pH‐sensitive calcium phosphate (MSNSr ‐CaP) or calcium phosphate zinc layer (MSNSr ‐CaZnP) are reported. It is demonstrated that the developed MSNs are taken up by human mesenchymal stromal cells and can efficiently promote osteogenesis under basic conditions, especially when multiple ions are introduced.